2022
DOI: 10.1159/000521104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Statins in Addition to Standard Therapy on Brain Perfusion and Neurocognitive Performance in Patients with Major Depressive Disorder

Abstract: <b><i>Introduction:</i></b> Major depressive disorder (MDD) is a prevalent condition which has a well-known association with ischemic cardiomyopathy, probably explained by an inflammatory mediator mechanism. Statins, besides reducing cholesterol production, have pleiotropic effects including anti-inflammatory activity. The goal was to evaluate the effect of statins as an addition to standard therapy on mood status, brain perfusion, and neurocognitive performance in MDD. <b><i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Numerous studies reported the effects of lipid-lowering therapies on the risk of dementia and impaired cognition (Table 4) 2,7,127–154 and for the treatment of dementia (Table 5). 155–168 Most of the higher-quality studies explored whether LDL-C–lowering therapies affected cognition.…”
Section: Lipid-lowering Drugs and The Risks Of Impaired Cognition And...mentioning
confidence: 99%
“…Numerous studies reported the effects of lipid-lowering therapies on the risk of dementia and impaired cognition (Table 4) 2,7,127–154 and for the treatment of dementia (Table 5). 155–168 Most of the higher-quality studies explored whether LDL-C–lowering therapies affected cognition.…”
Section: Lipid-lowering Drugs and The Risks Of Impaired Cognition And...mentioning
confidence: 99%
“…Of the seven included studies, all were completed and reported clinical outcomes ( 17 23 ). Six RCTs enrolled patients with MDD ( 17 20 , 22 , 23 ), while one enrolled patients with MDD or BD ( 21 ). One RCT enrolled patients with a history of coronary artery bypass surgery in the last 6 months ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies administered simvastatin and atorvastatin for 6–12 weeks ( 18 21 , 23 ). The primary endpoint was depression (indicated by HDRS score) in six RCTs ( 17 20 , 22 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations